A systematic review of the translation and validation methods used for the national comprehensive cancer network distress thermometer in non‐English speaking countries. Issue 8 (8th July 2022) - McElroy, Jane A.; Waindim, Flevis; Weston, Karry; Wilson, Gwendolyn
Abstract: Objective: The National Comprehensive Cancer Network (NCCN) distress thermometer (DT) was developed as a brief screening tool for detecting distress in cancer patients. Conceptually, distress was considered a more acceptable and inclusive term than other psychological terms such as depression or anxiety. It is used extensively in the United States and other English‐speaking countries. We aim to describe the translation and validation methods of the DT and describe the recommended cutoff scores used to identify cancer patients experiencing clinically significant distress. Methods: Nine bibliographic databases were searched using keywords to identify original research studies for non‐English speaking countries' cancer patients. Full articles were independently assessed for inclusion and data extraction by two authors. Results: The review of 4442 articles yielded 39 articles that validated the DT. We identified 20 languages in 25 countries. In all but one country, investigators were able to agree upon a word or phrase that meant distress in their native language that was subsequently validated against standardized instruments. Asian, Middle Eastern and European counties recommended cutoff score of 4 or 5 to identify clinically significant distress; however, European Union countries had a range of 2 to 7. Conclusions: Use of the translated DT with non‐English speaking cancer patients provides a simple and quick tool to identify high distress. Similar to NCCN, the cutoff score of 4 or 5 was suggested by 78% of the studies; however, more studies of different types of cancer and within and among more countries will strengthen a recommended global DT cutoff score.